2021
DOI: 10.1038/s41598-021-99291-z
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab reduces COVID-19 mortality and pathology in a dose and timing-dependent fashion: a multi-centric study

Abstract: Life-threatening COVID-19 is associated with strong inflammation, where an IL-6-driven cytokine storm appears to be a cornerstone for enhanced pathology. Nonetheless, the specific inhibition of such pathway has shown mixed outcomes. This could be due to variations in the dose of tocilizumab used, the stage in which the drug is administered or the severity of disease presentation. Thus, we performed a retrospective multicentric study in 140 patients with moderate to critical COVID-19, 79 of which received tocil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 38 publications
(36 reference statements)
0
22
0
Order By: Relevance
“…27 The timecourse for achieving measurable improvement after tocilizumab in COVID-19 has been reported as 5-6 days. 28,29 Alloimmunization is a common problem when transfusing patients with SCD. Only 35.2% of HHS episodes are associated with either a new alloantibody or new autoantibody.…”
Section: Discussionmentioning
confidence: 99%
“…27 The timecourse for achieving measurable improvement after tocilizumab in COVID-19 has been reported as 5-6 days. 28,29 Alloimmunization is a common problem when transfusing patients with SCD. Only 35.2% of HHS episodes are associated with either a new alloantibody or new autoantibody.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, study methodology varied widely regarding both use of biomarkers as inclusion criteria and timing, indication and dose of re-injection, with restrospective data suggesting a variable treatment effect according to disease severity, timing and dosage of treatment. 11,12 Whether identifying a subset of responders, optimal timing or need for higher doses or re-injection would impact survival remains an important unresolved question.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective work has suggested that treatment response is variable depending both on illness severity but also on treatment modalities. 11,12 Fine tuning the subset of patients most likely to benefit from such therapies as well as the ideal timing of administration and dosage can only be achieved by a better understanding of their effect on the immune response.…”
Section: Introductionmentioning
confidence: 99%
“…Also, increased interleukin-6 (IL-6) levels have been strongly associated with a shorter survival amongst patients suffering from SARS-CoV-2 [ 7 ]. The use of IL-6 inhibitors like tocilizumab has been considered since researchers have noted high concentrations of proinflammatory cytokines, such as IL-6 in severe SARS-CoV-2 infections [ 8 ]. It has also been shown to be effective in patients who develop hyperhemolysis in the setting of SCD [ 9 ].…”
Section: Discussionmentioning
confidence: 99%